Evaluation of Air Transportation Under Controlled Room Temperature for Pharmaceuticals - Badurina, Gordan; Majić, Zvonimir; Pavlin, Stanislav (Promet - Traffic&Transportation, 2012)
Pharmaceutical industry like aviation is one of the most regulated industries today. Shipping pharmaceutical products under defined time and temperature conditions is a challenge deriving from regulatory and product quality aspects. Good distribution practice should be valid throughout the distribution chain but regulatory issues are still short of strength in practice. Transportation should be considered as extended warehousing, still compliances are business rather than regulatory driven. The paper demonstrates deviations between shipping requirements and realistic capabilities of today’s commercial aviation in terms of maintenance of the controlled room temperature. Examples show cases of temperature deviations during transport realization. Suggestions are made on future research in the field of air transportation. KEY WORDS: good distribution practice, regulatory issues, controlled room